Microstructural and optical properties of ZnO thin films grown on InSb (111) substrates - Kim, TW; Lee, DU; Choo, DC; Lee, JH; Jung, M; Cho, J; Seo, KY; Yoon, YS (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
ZnO thin films were grown on InSb (111) substrates with the goal of producing high-quality ZnO films and ZnO/InSb heterostructures. Atomic force microscopy images showed that the root-mean-square average surface roughness of the ZnO film was 17.26 Angstrom , and X-ray diffraction measurements showed that the ZnO films grown on the InSb (111) substrates were preferential orientation in the [0001] crystal direction. Anger electron spectroscopy and bright-field transmission electron microscopy measurements showed that the ZnO/InSb heterostructures had no significant intermixing problems and had relatively sharp interfaces. The temperature dependence of the photoluminescence spectra showed dominantly the bound excition peaks at low temperature and the free exciton emission band at high temperature. These results indicate that ZnO (0001) preferential orientation textural films grown on p-InSb (111) substrates at low temperature hold promise for potential high-speed optoelectronic devices based on InSb substrates. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: PULSED-LASER DEPOSITION; MOLECULAR-BEAM EPITAXY; VAPOR-PHASE EPITAXY; ROOM-TEMPERATURE; GAN; SAPPHIRE; TRANSPORT; LAYERS; PLANE